2009
DOI: 10.1111/j.1439-0272.1997.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different staining and washing procedures on the results of human sperm morphology evaluation by manual and computerised methods

Abstract: The purpose of this study was to investigate the effect of different staining and washing procedures on the results of human sperm morphology evaluation by manual and computerised methods. Furthermore, it was intended to find the staining and washing combination which would provide optimal readability for computer-assisted sperm morphology evaluations. In phase one, four staining methods were evaluated for smears prepared from the resulting samples following a two times washing procedure. In phase two, 20 seme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
1
18
0
1
Order By: Relevance
“…Menkveld et al (1997) examined the relationship between human spermatozoa morphology and function of acrosome. Acrosome reaction evaluated at normal, small and large size in living and dead spermatozoa with triple stain.…”
Section: Discussionmentioning
confidence: 99%
“…Menkveld et al (1997) examined the relationship between human spermatozoa morphology and function of acrosome. Acrosome reaction evaluated at normal, small and large size in living and dead spermatozoa with triple stain.…”
Section: Discussionmentioning
confidence: 99%
“…In all these reports, the Diff-Quik â stain was found to be a suitable method, especially for the computer-assisted sperm morphology analysis (20), because the computer appears to recognize Diff-Quik â -stained sperm better than using other techniques. However, a direct comparison of the Diff-Quik method with the other stains appears to result in higher percentages of morphologically normal spermatozoa (17,31). Coetzee et al (32) found a significant bias of 1.6% with Diff-Quik â versus the Papanicolaou stain in favor of higher percentages of morphologically normal sperm using the Hamilton Thorne morphology analyzer integrated visual optical system (IVOS; Hamilton Thorne, Beverly, MA).…”
Section: Figurementioning
confidence: 97%
“…Because of the wet mount, spermatozoa could be lying on their sides rendering confusion with tapering forms by inexperienced observers (36). Another reason could be that the staining procedure itself is causing the sperm to swell, for which there is some indication (17). Other disadvantages are that these slides cannot be stored (36,37), as well as their high costs (33).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The ability of spermatozoa to bind to the zona pellucida, initiates the acrosomal reaction and binding to the oolemma that are necessary for a normal fertilization [Marnet et al 2000]. These phenomena occur in a subpopulation of spermatozoa with normal morphology [Menkveld et al 1997]. Moreover, Ron-el et al [1991] showed that human spermatozoal morphological defects are correlated with reduced male fertility, a lowered fertilization rate, poor embryo morphology, and reduced pregnancy rate.…”
Section: Introductionmentioning
confidence: 99%